IEO Evaluation of Exchange Rate Policy. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2007)
The IMF is charged by its Articles of Agreement and a 1977 Executive Board Decision to exercise surveillance over the international monetary system and members' exchange rate policies. The overriding question addressed by this evaluation is whether, over the 1999-2005 period, the IMF fulfilled this core responsibility. The main finding is that the IMF was simply not as effective as it needs to be in both its analysis and advice and in its dialogue with member countries. The evidence supporting this conclusion, along with other key findings, is set out in this report. The report also presents a detailed set of recommendations that could go a long way in improving the quality and effectiveness of IMF surveillance.